Risk Factors for the Development and Progression of Diabetic Kidney Disease in Patients with Type 2 Diabetes Mellitus and Advanced Diabetic Retinopathy - Kyung-Jin Yun; Hye Ji Kim; Mee Kyoung Kim; Hyuk-Sang Kwon; Ki-Hyun Baek; Young Jung Roh; Ki-Ho Song (Diabetes & Metabolism Journal, 2016)
BackgroundSome patients with type 2 diabetes mellitus (T2DM) do not develop diabetic kidney disease (DKD) despite the presence of advanced diabetic retinopathy (DR). We aimed to investigate the presence of DKD and its risk factors in patients with T2DM and advanced DR.MethodsWe conducted a cross-sectional study in 317 patients with T2DM and advanced DR. The phenotypes of DKD were divided into three groups according to the urine albumin/creatinine ratio (uACR, mg/g) and estimated glomerular filtration rate (eGFR, mL/min/1.73 m2): no DKD (uACR <30 and eGFR ≥60), non-severe DKD (uACR ≥30 or eGFR <60), and severe DKD (uACR ≥30 and eGFR <60). Mean systolic and diastolic blood pressure, mean glycosylated hemoglobin (HbA1c) level, and HbA1c variability (standard deviation [SD] of serial HbA1c values or HbA1c-SD) were calculated for the preceding 2 years.ResultsThe prevalence of no DKD, non-severe DKD, and severe DKD was 37.2% (n=118), 37.0% (n=117), and 25.8% (n=82), respectively. HbA1c-SD and the triglyceride/high density lipoprotein cholesterol (TG/HDL-C) ratio correlated positively with uACR and negatively with eGFR. Multiple linear regression analyses showed that the HbA1c-SD and TG/HDL-C ratio were significantly related with eGFR. Multiple logistic regression analyses after adjusting for several risk factors showed that HbA1c-SD and the TG/HDL-C ratio were significant risk factors for severe DKD.ConclusionThe prevalence of DKD was about 60% in patients with T2DM and advanced DR. HbA1c variability and TG/HDL-C ratio may affect the development and progression of DKD in these patients.